Investigation of viscoelastic properties in composite sandwich panels subjected to low-velocity impact: Experimental and numerical approaches. (May 2023) - Hosseinkhani, Milad; Ghavami, Hamed; Haghighi-Yazdi, Mojtaba; Mosavi Mashhadi, Mahmoud; Safarabadi, Majid
This study investigates the effect of viscoelastic properties in the numerical modeling of foam-filled sandwich panels when their composite facesheets are exposed to low-velocity impact loading. A finite element (FE) model is developed using the software package of ABAQUS and used to investigate the effect of both considering and ignoring the time-dependent behavior of composite laminate facesheets as well as the foam core. Material constitutive equations, damage characteristics, and failure modes are defined in a FORTRAN user-subroutine VUMAT. To characterize the material behavior of both polyurethane foam and glass/epoxy composite material, a set of experimental tests are conducted under compression, tension, and stress relaxation modes. To validate the numerical results, low-velocity impact tests at two energy levels of 9.81 and 17 joules are carried out on sandwich panels with foam core. The results of numerical simulations are found to be in good agreement with the experimental test results. It is shown that ignoring the viscoelastic properties in the composite laminate and the foam core can lead to deviations of up to 7% and 25%, respectively, from experimental results. The analysis reveals that, ignoring the viscoelastic behavior along the fiber-direction in the composite facesheets does no change the results considerably. The viscoelastic properties perpendicular to the fibers, however, has a more noticeable effect on the results due to the prevalence of the properties of the polymeric resin in that direction.